Discussing empirical research on the language and culture relationship to inform English as an additional/foreign language pedagogy and teacher education - Gil, Gloria; Luis, Renata Gomes (Revista Horizontes de Linguistica Aplicada, 2016)
Abstract In spite of the existence of a substantial body of theoretical literature that deals with the intersection of language and culture in the field of English as a foreign/additional (EA/FL) language teaching and learning, there are very few empirical studies that investigate this issue with real teachers and learners. Therefore, the objective of this paper is to review some of those empirical studies with a view to informing additional/foreign language pedagogy and teacher education. For that, the paper, first, summarizes some of the main theoretical issues by discussing the different ways in which the relationship of language and culture has been subjacent to EA/FL pedagogies. Then, the paper shows that there are three different types of language-and-culture-related empirical studies: on coursebooks, on teacher cognition, and on classroom interaction and teacher cognition. A review of these types of studies is made by discussing their main findings. Finally, the paper brings about some implications for the field from the findings of the empirical studies and proposes some topics for further research. Key-words: Culture and language relation. English as an additional/foreign language. Empirical studies. Resumo Apesar da existência de uma vasta literatura teórica que lida com a interseção entre língua e cultura na área de ensino e aprendizagem do inglês como língua adicional/estrangeira (LA/E), existem poucos estudos empíricos que investigam essa questão com professores e alunos reais. Portanto, o objetivo deste trabalho é revisar alguns desses estudos empíricos com o intuito de contribuir com a pedagogia e a formação de professores de inglês como LA/E. Para isso este trabalho, em primeiro lugar, resume algumas das principais questões teóricas, discutindo as diferentes maneiras em que a relação entre língua e cultura tem subjazido Ã s pedagogias do Inglês como LA/E. Em seguida, o trabalho mostra que há três tipos de estudos empíricos que lidam com a intersecção língua-cultura: estudos sobre livros didáticos, estudos sobre crenças/concepções de professores, e estudos sobre a interação de sala de aula e as crenças/concepções dos professores. Uma revisão desses diferentes tipos de estudos empíricos é feita ao se discutir suas principais descobertas. Finalmente, o artigo traz algumas implicações para a área a partir dos resultados dos estudos empíricos e propõe alguns tópicos para futuras pesquisas. Palavras-chave: Relação entre língua e cultura. Inglês com língua adicional/estrangeira. Estudos empíricos.